A Trusted-Group Criteria for Performing Trust Aware Routing in Mobile Networks (International Journal of Engineering and Computer Science, 2013)
Security is a significant issue in Wireless Mobile Networks. Intrusion of malicious nodes may cause serious impairment to the security. MANET often suffer from security attacks because of its features like open medium, changing its topology dynamically, lack of central monitoring and management, cooperative algorithms and no clear defense mechanism. A Mobile network is one of the most widely open network in which any intruder or the selfish node can easily perform an attack and affect the communication reliability. The presented work is about to define an effective and trustful communication approach over the network. . In this approach, a group management approach is defined. Each group will be managed by the base station itself. The group authentication will be done based on Diffie-Hellman algorithm